PENGARUH LATIHAN RANGE OF MOTION (ROM) AKTIF ASSITIF TERHADAP RENTANG GERAK SENDI PADA LANSIA YANG MENGALAMI IMMOBILISASI FISIK - Andri Setyorini; Niken Setyaningrum (STIKes Surya Global Yogyakarta, 2018)
Background: Elderly is the final stage of the human life cycle, that is part of the inevitable life process and will be experienced by every individual. At this stage the individual undergoes many changes both physically and mentally, especially setbacks in various functions and abilities he once had. Preliminary study in Social House Tresna Wreda Yogyakarta Budhi Luhur Units there are 16 elderly who experience physical immobilization. In the social house has done various activities for the elderly are still active, but the elderly who experienced muscle weakness is not able to follow the exercise, so it needs to do ROM (Range Of Motion) exercise. Objective: The general purpose of this research is to know the effect of Range Of Motion (ROM) Active Assitif training to increase the range of motion of joints in elderly who experience physical immobility at Social House of Tresna Werdha Yogyakarta unit Budhi Luhur. Methode: This study was included in the type of pre-experiment, using the One Group Pretest Posttest design in which the range of motion of the joints before (pretest) and posttest (ROM) was performed ROM. Subjects in this study were all elderly with impaired physical mobility in Social House Tresna Wreda Yogyakarta Unit Budhi Luhur a number of 14 elderly people. Data analysis in this research use paired sample t-test statistic Result: The result of this research shows that there is influence of ROM (Range of Motion) Active training to increase of range of motion of joints in elderly who experience physical immobility at Social House Tresna Wredha Yogyakarta Unit Budhi Luhur. Conclusion: There is influence of ROM (Range of Motion) Active training to increase of range of motion of joints in elderly who experience physical immobility at Social House Tresna Wredha Yogyakarta Unit Budhi Luhur.